Integrated Farming System: An ideal approach for developing more economically and environmentally sustainable farming systems for the Eastern Himalayan Region - ANSARI, M A; PRAKASH, N; BAISHYA, L K; P, PUNITHA; SHARMA, P K; YADAV, J S; KABUEI, G P; CH, KL LEVIS (The Indian Journal of Agricultural Sciences, 2014)
The present work was carried out at Chandel Khullen village of Chandel hill district of Manipur during 2010-11 to 2012-13. The average holding size of the farmer was 1.33 ha in 2010-11, 1.96 ha in 2011-12 and 2.21 ha in 2012-13. The tribal farmer adopted seven components, i e crop production, vegetables, fruits, piggery, backyard poultry, fishery and water management as suggested by ICAR Manipur Centre. In 2010-11, the paddy yield was 3.5 tonnes/ha as compared to 4.79 tonnes/ha in 2012-13. It was mainly due to adoption of improved package and practices. The cabbage and onion yield increased by 103 and 54 per cent, respectively after adoption of improved cultivation methods under integrated farming system. Similarly, the papaya and banana production was increased by 275 and 270 per cent. There was marked increase in pork, chicken, egg and fish production. In 2012-13, this system also provided significantly higher Rs per Re invested than that of the other 2010-11. In Manipur, women’s participation is more in farming system rather than men. In the same way, this farming system also gives more opportunity to women to engage in agriculture farming. Thus integrated farming system provides new venture for employment and sustainable development of livelihood for North Eastern people. The overall result revealed that the improved practices with different crop and animal components are an excellent approach for sustainable production, income generation and employment opportunity for the small and marginal rural households of Manipur.